(untitled) (Homoeopathy for All, 2026)
Challenges for Growth; Globally, it is the 2nd most popular system of medicines being used, after the Conventional Medicine. Imbalance between its potential, and accept ability. Gaps between the theoreti cal training and the practice. Re search oriented limited education. Outdated teaching methods. Lack of Integration. Disproportionate Job Opportunities. Societal Perceptions. Inter-system competition. Standard ization in medicines production, in cluding that of Raw Material. Glob ally acceptable regulations and their compliance. Harmony imbalance between profession, Academics & Industry. Encouraging entrepreneur ship. Way forward, with active participation, and collaboration.